2021
DOI: 10.1136/gutjnl-2020-323132
|View full text |Cite
|
Sign up to set email alerts
|

Linked Colour imaging for the detection of polyps in patients with Lynch syndrome: a multicentre, parallel randomised controlled trial

Abstract: ObjectiveDespite regular colonoscopy surveillance, colorectal cancers still occur in patients with Lynch syndrome. Thus, detection of all relevant precancerous lesions remains very important. The present study investigates Linked Colour imaging (LCI), an image-enhancing technique, as compared with high-definition white light endoscopy (HD-WLE) for the detection of polyps in this patient group.DesignThis prospective, randomised controlled trial was performed by 22 experienced endoscopists from eight centres in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 40 publications
0
13
1
Order By: Relevance
“…For the number of SSLs per patient in 2 studies, LCI also did not increase the detection of SSLs per patient compared with WLI. 3,6 The results of the current study (which shows the superiority of LCI over WLI for SSLs detection) are not consistent with these studies, and they are not consistent with the pooled results of a meta-analysis. 2 Therefore, such differences between the results need to be explained.…”
Section: Linked Color Imaging For the Detection Of Colorectal Sessile...contrasting
confidence: 91%
See 2 more Smart Citations
“…For the number of SSLs per patient in 2 studies, LCI also did not increase the detection of SSLs per patient compared with WLI. 3,6 The results of the current study (which shows the superiority of LCI over WLI for SSLs detection) are not consistent with these studies, and they are not consistent with the pooled results of a meta-analysis. 2 Therefore, such differences between the results need to be explained.…”
Section: Linked Color Imaging For the Detection Of Colorectal Sessile...contrasting
confidence: 91%
“…In the previous studies, only one article adopted a mixed study population, 5 and the rest only included people who are intended for screening or surveillance colonoscopies. 3,4,6,7 This seems to be one of the reasons for the inconsistencies with the current findings. However, indications for colonoscopy do not appear to be a factor influencing SSLs detection in the present study.…”
Section: Linked Color Imaging For the Detection Of Colorectal Sessile...mentioning
confidence: 52%
See 1 more Smart Citation
“…This prospective study is a prespecified post-hoc analysis of the LCI-LYNCH trial [13]. The study was conducted in in eight centers in Belgium, Italy, the Netherlands, Poland, Spain, and the United Kingdom.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a 2020 meta-analysis of 7 studies including 3097 patients demonstrated improved adenoma detection (RR 1.26, P < 0.001), particularly in the right colon (RR 2.68, P < 0.001) and a mean of 0.27 additional adenomas detected per colonoscopy[ 85 ]. In a high-risk population of patients with HNPCC, LCI was found to improve ADR compared to HD-WLI (36.3% vs 25.6%, P = 0.04)[ 86 ]. Interestingly, while advanced imaging such as NBI appears to have a greater impact when used by experienced endoscopists, a 2021 study by Hasegawa et al [ 87 ] found a strong negative correlation between the baseline ADR with HD-WLI and the improvement ratio, indicating that perhaps the familiar colour pattern allows effective use by non-expert proceduralists.…”
Section: Polyp Detectionmentioning
confidence: 99%